Protection of Children's Rights in Post-Divorce Custody Disputes Comprehensive Study on the Best Interests of Children - Khotim, Ahmad (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
In the framework of Indonesian positive law, it is only the KHI that assigns child custody to the mother. Other legal provisions merely indicate that both parents are responsible for their children's care without clarifying which parent is awarded custody following a divorce. Various rulings exist that have granted custody to mothers, yet there are also instances where custody has been awarded to fathers. This creates ambiguity regarding the determination of child custody post-divorce. The objective of this study is to assess the most effective indicators for judges to consider in making child custody decisions, grounded in the principle of prioritizing the child's best interests. The methodology employed for this research is prescriptive normative legal analysis with a conceptual focus. Findings indicate that several factors can be utilized when deliberating on custody matters, including the child's wellbeing, the behavior of the parents, cooperation between them, and the allocation of parenting time. Should there be a need for additional factors, judges are permitted to incorporate these, provided they align with the principle of the child's best interests.